Defining the Notion ‘Youth Entrepreneurship’ in View of Including in it Specific Features of Entrepreneurial Resource Use - A. A. Shpileva (Вестник Российского экономического университета имени Г. В. Плеханова, 2024)
The article studies possible definitions of the notion ‘youth entrepreneurship’ with regard to including in it specific features of entrepreneurial resource use, such as generation of business ideas (initiatives), implementation of business-projects and management of their realization. The author proposed to summarize definitions that take into account both age characteristics of young people and level of their education and features of entrepreneurial resource realization, such as entrepreneurial capital, skills, knowledge, motivation and innovation abilities. Within the frames of the article the model of education lever was put forward and discussed that shows the impact of state support tools being realized in state education policy on the development of youth entrepreneurship. The research findings can be useful for investigators, practical workers and state bodies dealing with the development of youth entrepreneurship.